Upaya Emma Watson Dalam Mewujudkan Kesetaraan Gender Melaui Kampanye He for She - Septian Joski Cladino; Zulkifli Harza; Maryam Jamilah (Hubungan Internasional Universitas Andalas, 2024)
Celebrities do not only focus on being stars in the world of entertainment but are also able to be communicator in the political and social world. United Nation Women appoints Emma Watson, a celebrity known through the Harry Potter series, as a ambassador or communicator as well as launch He for She campaign. This campaign aims to achieve gender equality which involves men as agents. Gender problems that occur in parts of the world cause anxiety, therefore the United Nation Women launched the He for She campaign. The purpose of this study is to see how Emma Watson's efforts in gender equality activities through the He for She campaign. In analyzing, the writer uses the concept of Strategic Communication to see the form of efforts made by Emma Watson. This research is a qualitative research using a descriptive analysis approach in the research range from 2010 to 2020. The results of the research obtained are that the efforts made by Emma Watson resulted in He for She campaign launch speech, He for She campaign IMPACT 10X10X10 speech, He for She Arts week launch speech, Uruguay Parliament building visit, He for She campaign second anniversary speech. Key Words: Emma Watson, He for She, gender equality, efforts, strategic communication.